2016
DOI: 10.1002/sej.1221
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Alliances of Entrepreneurial Firms: Value Enhancing Then Value Destroying

Abstract: Research summary: Based on the RBV and dynamic capabilities, this study explains the relationship between alliance formation and the private (pre-IPO) entrepreneurial firm's market performance. Findings show that while alliance formation positively and significantly affects the market performance of venture-backed firms in the software industry, forming a comparatively large number of alliances hurts these firms' market valuations.Managerial summary: Entrepreneurial firms are better off entering a select numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 98 publications
1
36
0
1
Order By: Relevance
“…However, other DCs are worth of further investigation in this context. Prominent examples of these DCs are, for instance, the alliance capability (e.g., Moghaddam et al, 2016 ), the transnational product development capability ( Subramaniam and Venkatraman, 2001 ), and the marketing capability (e.g., Danneels, 2008 , 2012 , 2016 ; Song et al, 2005 ). The alliance capability provides firms with access to novel resources and complementary assets; which favors entry into new product-markets; the transnational product development capability allows firms to leverage knowledge from sources in different countries and develop new products simultaneously for multiple markets.…”
Section: Discussionmentioning
confidence: 99%
“…However, other DCs are worth of further investigation in this context. Prominent examples of these DCs are, for instance, the alliance capability (e.g., Moghaddam et al, 2016 ), the transnational product development capability ( Subramaniam and Venkatraman, 2001 ), and the marketing capability (e.g., Danneels, 2008 , 2012 , 2016 ; Song et al, 2005 ). The alliance capability provides firms with access to novel resources and complementary assets; which favors entry into new product-markets; the transnational product development capability allows firms to leverage knowledge from sources in different countries and develop new products simultaneously for multiple markets.…”
Section: Discussionmentioning
confidence: 99%
“…This research gap warrants further investigation because theory emphasizes that a firm's ability to identify and assimilate external resources and knowledge may be more important for performance and growth than the firm's initial stock of resources and knowledge (Cohen & Levinthal, 1990;Nason & Wiklund, 2015). Moreover, access to competencies and resources is particularly important for new and small ventures, which typically possess limited internal resources but may be able to compensate for such shortcomings by relying on alliances and linkages with external actors (Arikan & McGahan, 2010;Moghaddam, Bosse, & Provance, 2016;Mohr, Garnsey, & Theyel, 2013). USOs, in particular, face challenges in developing the competencies needed to commercialize novel technologies with uncertain market potential, and the university environment may contribute to these challenges (Rasmussen, Mosey, & Wright, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, competitive dynamics research has suggested that the availability and direction of attention within an organization affects how firms identify and respond to rivals and also the types of actions enacted based on the attention of managers within the firm (Kilduff, 2019;Ridge et al, 2017). Similarly, researchers interested in cooperative actions have found that while alliance management capabilities increase with experience, attentional constraints limit the extent to which the firm is capable of maximizing value across a larger alliance portfolio (Moghaddam, et al, 2016). Considering the attentional demands of competitive and cooperative actions, along with the potential for conflicting demands for attention within the firm, the ABV provides a foundation for understanding how attentional constraints within the firm are likely to impact the effectiveness of a firm's competitive and cooperative action repertoire management.…”
Section: The Attention-based View Of the Firmmentioning
confidence: 99%
“…While firms may be able to improve IOR outcomes by focusing attention, a firm's limited capacity of attention would suggest that engaging in too many cooperative actions may have the opposite effect (Lahiri and Narayanan, 2013) by increasing coordination costs (Gulati et al, 2012) and, ultimately, shaping the relationship between cooperative action volume and performance (Rothaermel, 2001). Furthermore, as volume of cooperative actions increases, a lack of attention leads to routinization and an overreliance on heuristics such that it hinders a firm's ability to capture value from new and existing cooperative IORs (Heimeriks, 2010;Moghaddam et al, 2016;Siggelkow, 2001). The challenges and risks associated with individual IORs are likely to be further amplified when they are examined holistically at the firm-level among a larger repertoire of cooperative IORs.…”
Section: The Diminishing Returns Effect Of Action Volume On Firm Performancementioning
confidence: 99%